E-Learning Security Issues and Challenges: An Analytical Study with Statistical Evaluation (Comprehensive Journal of Science, 2025)
E-learning platforms have grown rapidly in recent years, yet this expansion has exposed educational institutions to a wide range of cybersecurity threats. Prior research reports increasing cases of data breaches, weak authentication, phishing, and ransomware attacks that directly affect learners and instructors (Salvador, 2021; Oroni, 2025). This study investigates the most common security issues in e-learning environments and evaluates user perceptions using a quantitative approach. A total of 150 participants students, instructors, and IT specialists completed a structured questionnaire measuring awareness, vulnerability, and previous exposure to threats. Descriptive statistics, Cronbach’s Alpha, Chi-Square, and ANOVA tests were applied to verify reliability and identify significant differences among user groups. Results show that data privacy concerns, phishing attempts, and authentication weaknesses are perceived as the most critical challenges. Findings highlight the urgent need for stronger security policies, improved technical safeguards, and enhanced user awareness to ensure a safer digital learning ecosystem.
Keywords: E-learning security, cybersecurity challenges, data privacy, authentication weaknesses, phishing attacks, online learning systems, cyber awareness, digital education, online proctoring privacy, cloud-based learning security, ransomware in education, user vulnerability, educational technology security, LMS security, ICT policy, cyber risk perception, higher education security, digital transformation, threat detection, information security in education.